STUDY OF LONG-TERM TREND IN RIVER DISCHARGE OF SUTLEJ RIVER (N-W HIMALAYAN REGION) - Dharmaveer Singh; Rajan D. Gupta; Sanjay K. Jain (Geography, Environment, Sustainability)
Sutlej basin, a mountainous river basin is located in N-W Himalayan region. This basin has highest potential for hydropower generation as compared to other basins of Indus River system. Recent studies have revealed rise in mean annual surface temperature which will modify pattern of Sutlej River flow in this basin. The present paper has aimed for studying annual and seasonal patterns of river discharge at different gauging sites of Sutlej River basin (middle catchment), India. The study has been performed over three gauging sites, namely, Kasol, Sunni and Rampur located under different physiographic and climatic conditions. The daily historical records (1970-2010) of 41 years river discharge data have been employed for statistical analysis. The annual and seasonal Standardized Discharge Indices (SDI) has been derived in order to preserve uniformity and facilitate comparison between flows of Sutlej River at different sites. Mann-Kendall (MK) test, a non-parametric test method, has been applied to detect trend in annual and seasonal SDI for periods 1970-2010. Decadal (annual and seasonal) patterns in SDI have also been discussed. The results of annual and seasonal trend analysis have revealed decreasing trends in SDI at all the gauging sites. The trend in annual SDI is statistically significant (95% confidence level) at Rampur (0,04 cumec/year) and insignificant at Kasol (0,02 cumec/year) and Sunni (0,01 cumec/year) respectively. The study of annual decadal change in SDI at all the sites shows that reduction in river discharge has occurred in the decade of 2001-2010. Before this, continuous rise in annual discharge has been reported at all the sites from decades 1970-1980 to the last decade of 20th century (1991-2000). The decline in river flow may affect agriculture and electricity production as well as there may be problems related with drinking water. The present study is expected to be useful for planning water resources related projects that can be undertaken in the Sutlej basin.